High‐Loading Co Single Atoms and Clusters Active Sites toward Enhanced Electrocatalysis of Oxygen Reduction Reaction for High‐Performance Zn–Air Battery - Zhang, Mengtian; Li, Hao; Chen, Junxiang; Ma, Fei‐Xiang; Zhen, Liang; Wen, Zhenhai; Xu, Cheng‐Yan (Advanced functional materials, 2023)
The development of precious‐metal alternative electrocatalysts for oxygen reduction reaction (ORR) is highly desired for a variety of fuel cells, and single atom catalysts (SACs) have been envisaged to be the promising choice. However, there remains challenges in the synthesis of high metal loading SACs (>5 wt.%), thus limiting their electrocatalytic performance. Herein, a facile self‐sacrificing template strategy is developed for fabricating Co single atoms along with Co atomic clusters co‐anchored on porous‐rich nitrogen‐doped graphene (Co SAs/AC@NG), which is implemented by the pyrolysis of dicyandiamide with the formation of layered g‐C3N4 as sacrificed templates, providing rich anchoring sites to achieve high Co loading up to 14.0 wt.% in Co SAs/AC@NG. Experiments combined with density functional theory calculations reveal that the co‐existence of Co single atoms and clusters with underlying nitrogen doped carbon in the optimized Co40SAs/AC@NG synergistically contributes to the enhanced electrocatalysis for ORR, which outperforms the state‐of‐the‐art Pt/C catalysts with presenting a high half‐wave potential (E1/2 = 0.890 V) and robust long‐term stability. Moreover, the Co40SAs/AC@NG presents excellent performance in Zn–air battery with a high‐peak power density (221 mW cm−2) and strong cycling stability, demonstrating great potential for energy storage applications. High‐loading Co single atoms and Co atomic clusters co‐anchored on porous‐rich nitrogen‐doped graphene (Co SAs/AC@NG) is constructed via a facile self‐sacrificing template strategy. The Co40SAs/AC@NG catalyst demonstrates remarkable performance with a half‐wave potential of 0.890 V for oxygen reduction reaction and a large power density of 221 mW cm−2 toward Zn–air battery.